Increase in efficiency of media utilization for recombinant protein production in Chinese hamster ovary culture through dilution - Thombre, Shreya; Gadgil, Mugdha (Biotechnology and Applied Biochemistry, 2011)
Animal cells are extensively used for the large-scale production of recombinant proteins. Processes and genetically engineered cell lines have been developed to enhance longevity of the culture and increase protein productivity. In this study, we tested the effect of diluting a culture of Chinese hamster ovary (CHO) cells with phosphate-buffered saline (PBS) on cell growth and efficiency of media utilization. An immunoglobulin G-expressing CHO cell line was cultured in CD CHO media followed by dilution of the culture with PBS after the end of the exponential phase. A 28% and 61% increase in protein yield per milliliter of media was observed in the diluted culture in the batch and fed-batch mode with glucose and protein hydrolysate feeding, respectively. To aid in analyzing the potential causes of this observed increase, an unstructured mathematical model was constructed using previously reported kinetics to simulate cell growth, nutrient utilization, and protein production. The model predicts an increase in recombinant protein yield per milliliter of media in PBS diluted cultures under both batch and fed-batch conditions, and suggests that this observed increase could at least partly be due to a decrease in inhibitor concentration in the diluted culture.
Keywords: chemically defined media; culture dilution; glucose consumption; inhibitor formation; recombinant protein yield